Role of color Doppler imaging in borderline size appendix-Simple method to improve specificity for appendicitis - Kumar, Dr. Naveen; K R, Dr. Prathasarathya; Reddy, Dr. Vijaymohana; Naganus, Dr. Gowri (International Journal of Scientific Research and Management (IJSRM), 2017)
Aims and objective:To differentiate between the normal appendix from inflamed appendix on color Doppler imaging.Continuous intramural vascular signal measuring at least 3mm on color Doppler imaging is highly specific forappendicitis in borderline-size appendix.Materials and method:Equipment and Method:All patients were scanned with a single ultrasound machine and 9–15-MHz transducers (GE Healthcare).Study design:Prospective studySample size:50 patients referred to radiology dept with possible appendicitis from 2015 to 2017.Source of the data:Patients coming to the department of radio diagnosis at SSIMS & RC Davangere with a clinical history of painand tenderness in RIF and all patients who had undergone graded-compression sonography for possibleappendicitis and whose appendices were of diagnostically borderline size (6–8 mm maximum outer diameter).Results:Of the 50 patients, 17had type 1 flow (of whom 3 had appendicitis); 13 had type 2 flow (of whom 11 hadappendicitis); and 20had absent flow (of whom 5had appendicitis).Conclusion:Graded-compression US remains our first-line method in the evaluation of patients referred with clinicallysuspected acute appendicitis.Type II flow (Continuous linear or curvilinear flow >3mm) within the wall of the appendix is highly specific,yet insensitive, for appendicitis in borderline sized appendix.Type I flow (Punctuate dispersed signal) is neither sensitive nor specific for appendicitis and can be seennormal appendix.